Improved Service Learning Outcomes Using D'volleyball Learning Application - Destriani Destriani; Destriana Destriana; Ahmad Richard Victorian; Hartati Hartati; Wahyu Indra Bayu; Okky Putra Alwin; Herri Yusfi (Altius: Jurnal Ilmu Olahraga dan Kesehatan, 2022)
This study aims to determine the improvement of service learning outcomes for high school students using the D'Volleyball Learning Application learning media at Senior High School No 1 Indralaya Utara. This learning application can be accessed via the link https://play.google.com/store/apps/details?id=com.dvolleyball.learning or on the play store by searching for D'Volleyball Learning Application. This D'Volleyball Learning Application contains various features regarding volleyball game material, assignments, learning videos, and assessments. This study uses a classroom action research method, with the number of research subjects as many as 22 class XII students at Senior High School No1 Indralaya Utara. This research uses the type of classroom action research conducted in two cycles. Data collection techniques used in this study were tests and observations. Each cycle has four stages, namely planning, implementation, observation, and reflection. The research subjects were 22 students including 10 female students and 12 male students. The results in this classroom action research obtained data on the initial conditions or pre-cycle of 36.4% of students completed, and 63.6% incomplete, then the results of the first cycle of student learning outcomes amounted to 63.6% with complete criteria, and amounted to 36.6% did not complete, then the results of the research in cycle 2 increased by 36.6% so that all students completed learning in cycle 2. So the conclusion is that the D'Volleyball Learning Application can improve the service learning outcomes of volleyball for class XII students at Senior High School No 1 Indralaya Utara.